The Development of Arabic Learning Model by Using Multimedia of Computer at UIN STS Jambi - Yogia Prihartini; Wahyudi Wahyudi; Aliasar Aliasar; Mukhaiyar Mukhaiyar; Ungsi AOM (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This research and development result in a learning model that could be used to improve oral communication that was divided into five different learning phase, which is, orientation phase, ordering command phase, role exchange phase, structured practice phase, and guided practice phase. It could also improve one’s understanding of arabic grammar/qawaid (nahwu wa sharfi) which consists of elements in Arabic language that consist of Letters (harf), Words (kalimatu), Sentences (jumlatu), sibhuljumlah and articles (uslub) and fit into Arabic grammar. The result of this study implies that development result study model emphasize in college students’ activities in their learning process. The learning process done by the lecturers using Arabic language as the language of instruction started by the pronunciation of the vocabularies and it’s demonstration without translating it into Bahasa Indonesia. After they were capable of demonstrating the acquired vocabularies, college students trained in reproducing the language orally using question and answer activities, whether structurally, or guided. The study results showed that the quality of this multimedia teaching of Arabic language fall into the ‘fine’ category, acquiring average score of 43.92 and ideal percentage of 87.85%.